1999
DOI: 10.1006/viro.1998.9534
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Influenza Virus-Infected SCID Mice with Nonneutralizing Antibodies Specific for the Transmembrane Proteins Matrix 2 and Neuraminidase Reduces the Pulmonary Virus Titer but Fails to Clear the Infection

Abstract: Antibodies (Abs) can contribute to the cure of a viral infection, in principle, in two ways by: (1) binding to infected cells and thereby reducing the production of progeny virus [here termed cell-targeting (CT) activity] and (2) reacting with released progeny virus and thereby inhibiting the spread of the infection [termed virus neutralizing (VN) activity]. We have previously shown that a pulmonary influenza virus infection in severe combined immunodeficient mice could be cured by treatment of these mice with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
98
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 52 publications
9
98
1
1
Order By: Relevance
“…This is in line with the requirement for Th1 cytokine responses, such as IFN-g for Ig class switching and associated enhancement of cellular antiviral responses (22)(23)(24). This is further confirmed by the observation that a subtype switch from IgG1 anti-M2e monoclonal 14C2 to the switch variant anti-M2e IgG2a improves its protective efficacy in vivo (17,25).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…This is in line with the requirement for Th1 cytokine responses, such as IFN-g for Ig class switching and associated enhancement of cellular antiviral responses (22)(23)(24). This is further confirmed by the observation that a subtype switch from IgG1 anti-M2e monoclonal 14C2 to the switch variant anti-M2e IgG2a improves its protective efficacy in vivo (17,25).…”
supporting
confidence: 69%
“…Indeed, protective immunity can be transferred from vaccinated animals to naive recipients by serum (11,(13)(14)(15)(16). Moreover, anti-M2e mAbs protect wild-type and immunodeficient scid recipient mice against influenza A virus infection (17)(18)(19). Although a contribution by M2e-specific T cell responses to protection cannot be ruled out, M2e-specific serum Abs are crucial for immune protection.…”
mentioning
confidence: 99%
“…Unlike HA-specific Abs (22,25), M2e-specific Abs cannot prevent virus from initiating an infection or resolve an established infection, but they can diminish the yield of infectious virus and thus inhibit progression of the infection (23,31). We were interested in establishing an experimental system in which the growth-restricting activity of M2e-specific Ab and the capability of influenza virus to escape it could be best assessed in vivo.…”
Section: Progression Of a Nasal Pr8 Virus Infection In Scid Micementioning
confidence: 99%
“…Indeed, the majority of human epidemic strains isolated since 1918 share the same M2e protein sequence. Second, several studies in mice have shown that M2e-specific Abs restrict influenza virus replication and reduce morbidity and mortality (6,19,23,24,31). Furthermore, a recent study in ferrets, the animal model considered most prognostic for human influenza, has demonstrated protective activity of M2e-specific immunity (6), and sera from rhesus monkeys immunized with a M2e-carrier conjugate have been shown to exhibit protective activity upon transfer into mice (6).…”
mentioning
confidence: 99%
“…However, antibodies raised against non-HI epitopes or other viral proteins [20][21][22][23], as well as cell mediated immunity (CMI) (reviewed in [24]), clearly play a role in the heterologous cross-reactive immune responses (Het-I) against influenza virus infection. Exposure to live virus or MLV vaccine is likely to have a more robust response against many viral epitopes through heightened cell-mediated immune activation and through the induction of mucosal immunity.…”
Section: Introductionmentioning
confidence: 99%